Recent Advancements in Breast Cancer Therapies and Biomarkers: Mechanisms and Clinical Significance - Husain, Arbab; Khan, Hamda; Fatima, Jamal e; Siddiqui, Shirjeel Ahmad; Singh, Akash Deep; Husain, Adil; Pandey, Shivam; Kant, Ravi; Khanam, Afreen; Pandey, Pratibha; Khan, Fahad (Current Pharmaceutical Biotechnology, 2025)
Breast cancer remains a critical health concern, requiring continual innovation in treatment to improve patient outcomes. The continuous obstacles in therapy and the need for novel techniques underline the importance of making advances in this discipline. Precision medicine has emerged as a viable method, with genomic profiling and molecular subtyping allowing for targeted therapy based on distinct breast cancer subtypes. This strategy is supplemented by advances in early detection and screening, with technologies like liquid biopsy promising earlier and more accurate diagnosis. The introduction of immunotherapy has transformed breast cancer treatment by using the body's immune system to combat cancer. Recent discoveries, particularly combination medicines, attempt to circumvent resistance mechanisms and improve treatment success. Furthermore, including lifestyle therapies such as nutrition, exercise, and psychological support has been demonstrated to reduce breast cancer risk and strengthen survivability rates. Survivorship programs serve an important role in comprehensive care by addressing long-term needs and enhancing survivors' quality of life. Investigating innovative therapeutic approaches, such as developing cancer vaccines, epigenetic modulators, and RNA interference (RNAi) therapy, provides new treatment options. Fostering collaboration among healthcare personnel through shared decision-making and tumor committees is essential for the integration of multidisciplinary care, which ensures patient-centered care. Although advancements have been made, there are still numerous obstacles to overcome in the implementation of these future directions. To effectively confront these obstacles, it is imperative to capitalize on opportunities for innovation and collaboration. It is imperative to address ethical, social, and economic factors in the advancement of breast cancer care to ensure that innovations are equitable and accessible. In conclusion, the future of breast cancer management is bright since substantial improvements are on the verge of turning patient treatment into a completely different experience. For these breakthroughs to become a reality, it is necessary to maintain research efforts, advocate for them, and work together. The dedication to innovation and the joint effort to overcome current problems are the two important factors that will determine whether or not breast cancer treatment and surviving will have a better future.
Keywords: multidisciplinary care